First cytogenetic characterization of Loricaria simillima (Loricariidae, Siluriformes) from Paraná River (Argentina) with emphasis in cytotaxonomy of Loricaria - Benitez, Mauricio Fabián (2017)
This work aims to establish some cytogenetic characteristics of Loricaria simillima from Paraná River. The obtained results show that L. simillima has a 2n = 64 diploid number, with 12 metacentric, 12 sub-metacentric and 40 sub-telo/acrocentric chromosomes. No chromosomal differences were found between sexes. The nucleolus organizer region (NOR) revealed by Ag-NOR was located next to the centromeric region in the short arm of pair 8. The C-bands were pale and detected in pericentromeric regions of the most chromosomes and interstitiallyon a sub-metacentric pair, coincident with secondary and NORs constriction. A conspicuous interstitial band on an acrocentric chromosome was also observed. Finally DAPI and CMA3 fluorescent bandings showed G-C richness at the NOR region. Present data evidence a great similarity among L. simillima, L. cataphracta and L. carinata, reinforcing the hypothesis that they constitute a closely related phylogenetic group.